INFLUENCE OF THE SITE CONDITIONS ON THE LONG TERM EVOLUTION OF THE WEED FLORA AND OF ONION (ALLIUM CEPA L.)’ PRODUCTION IN THE NORTH OF BENIN - BELLO, S.; Ahanchede, A.; AMADJI, GUILLAUME LUCIEN; Maliki, R. (My University, 2019)
The present study has been conducted in order to put into relation the continuous farming duration, the soil texture and fertility level, the dominant species presence, the weed covering degree with the onion’s bulb yield. it aims to determine also the term of putting onion’s plots into fallow or abandonment in the North-East of Benin. Thirty-two onion plots have been considered in two villages named Kargui and Toumboutou, located respectively in the communes of Malanville and Karimama. Collected data have been submitted to one factor regression analysis with the general linear model and to the principal components analysis (PCA). Results have shown a quanlitative evolution of the flora characterized, depending on the soil texture, which is characterized by the erosion of the specific diversity. and its specialization by Cyperus rotundus and Portulaca quadrifida in a long term. This transformation of the flora in relation with the continuous crop duration is relative to the soil fertility and the onion’ yield declining, which cause abandonment or fallow lying of plots for which these species are indicators. Concerned weeds are Boerhavia diffusa, Commelina benghalensis, Commelina diffusa, Cyperus tuberosus and especially Cyperus rotundus and Portulaca quadrifida which appear as dominant with the continuous cropping duration.
Keywords: Continuous cropping duration; fertility; manual weeding; onion; specy; yield